2003
DOI: 10.1046/j.1460-9568.2003.02867.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory survival mechanisms in acetylcholinesterase knockout mouse

Abstract: Cholinergic neurotransmission ensures muscle contraction and plays a role in the regulation of respiratory pattern in the brainstem. Inactivation of acetylcholinesterase (AChE) by organophosphates produces respiratory failure but AChE knockout mice survive to adulthood. Respiratory adaptation mechanisms which ensure survival of these mice were examined in vivo by whole body plethysmography and in vitro in the neonatal isolated brainstem preparation. AChE-/- mice presented no AChE activity but unaffected butyry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 41 publications
0
51
0
1
Order By: Relevance
“…2E). A similar role for BChE was Twitch potentiation is considered to arise from suggested by Chatonnet et al, 7 based on their results multiple muscle action potentials following a single with the selective BChE inhibitor, bambuterol. stimulus, which may be triggered by repetitive nerve A second possible mechanism for maintenance impulses (backfiring) or from a single prolonged of tetanic tension in AChE-/-mice is downregulation endplate potential.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…2E). A similar role for BChE was Twitch potentiation is considered to arise from suggested by Chatonnet et al, 7 based on their results multiple muscle action potentials following a single with the selective BChE inhibitor, bambuterol. stimulus, which may be triggered by repetitive nerve A second possible mechanism for maintenance impulses (backfiring) or from a single prolonged of tetanic tension in AChE-/-mice is downregulation endplate potential.…”
mentioning
confidence: 83%
“…In AChE-inhibmice. 3 4 Downregulation of both nAChRs and ited muscle, reductions in tension during repetitive mAChRs was reported by Chatonnet et al, 7 who stimulation reflect an underlying desensitization of found reduced sensitivity to nicotine and muscarine nAChRs following accumulation of ACh.12" 7 Desenin isolated brainstem preparations of AChE--mice. sitization is suggested by the decrease in the ampliInhibition of AChE activity results in repeated tude of successive responses at 20 Hz and by tetanic binding of ACh to nAChRs, a key factor responsible fade at 200 Hz and 400 Hz (Fig.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…It has been reported that a 30-mg dose of bambuterol in adult humans inhibits 90% of the plasma BChE and that the bambuterol-induced BChE deficiency causes succinylcholine apnea (Bang et al, 1990). AChE Ϫ/Ϫ mice die when they are treated with bambuterol, suggesting that inhibition of BChE is responsible for their death (Xie et al, 2000;Chatonnet et al, 2003). Because no drug is completely specific in vivo, it was possible that other enzymes were also involved in this response.…”
mentioning
confidence: 99%
“…These and other findings suggest the involvement of both muscarinic and nicotinic receptors in the anticholinesterase-induced central respiratory failure (31).…”
Section: Central Component Of Anticholines Teraseinduced Respiratormentioning
confidence: 63%